Prosodic Restructuring In Somali Nominal Constructions - Downing, Laura; Nilsson, Morgan (My University, 2019)
This paper investigates variability in the realization of High tones in some nominal constructions of Somali. Previous work on Somali tone suggests that most determiners and all nominal modifiers should realize a High tone when they combine with the noun they modify. However, our study finds that there is considerable variability in the realization of High tones on nominal determiners and modifiers, with the High tone often not realized. This phenomenon of variability in tone realization is quite reminiscent of Swedish, which shares with Somali the property that tone realization is culminative within some prosodic domain. Recent work on Swedish has argued that variable non-realization of High tone is best analyzed as prosodic restructuring: reducing the number of culminative tonal domains in a construction necessarily leads to a reduction in the number of surface High tones. We argue that prosodic domain restructuring also provides the most plausible analysis of High tone reduction in Somali nominals.
Keywords: Somali; nominal constructions; High tones